Fluorescence-guided optical coherence tomography imaging for colon cancer screening: a preliminary mouse study - Iftimia, Nicusor (Optical Society of America, 2011)
A new concept for cancer screening has been preliminarily investigated. A cancer targeting agent loaded with a near-infrared (NIR) dye was topically applied on the tissue to highlight cancer-suspect locations and guide optical coherence tomography (OCT) imaging, which was used to further investigate tissue morphology at the micron scale. A pilot study on ApcMin mice has been performed to preliminarily test this new cancer screening approach. As a cancer-targeting agent, poly(epsilon-caprolactone) microparticles (PCLMPs), labeled with a NIR dye and functionalized with an RGD (argenine-glycine-aspartic acid) peptide, were used. This agent recognizes the α(ν)β(3) integrin receptor (ABIR), which is over-expressed by epithelial cancer cells. The contrast agent was administered topically in vivo in mouse colon. After incubation, the animals were sacrificed and fluorescence-guided high resolution optical coherence tomography (OCT) imaging was used to visualize colon morphology. The preliminary results show preferential staining of the abnormal tissue, as indicated by both microscopy and laser-induced fluorescence imaging, and OCT’s capability to differentiate between normal mucosal areas, early dysplasia, and adenocarcinoma. Although very preliminary, the results of this study suggest that fluorescence-guided OCT imaging might be a suitable approach for cancer screening. If successful, this approach could be used by clinicians to more reliably diagnose early stage cancers in vivo.